Perirenal Fat Thickness: A Surrogate Marker for Metabolic Syndrome in Chinese Newly Diagnosed Type 2 Diabetes - Guo, Xiu Li; Tu, Mei; Chen, Yang; Wang, Wei (Frontiers in Endocrinology, 2022)
Abstract Objective: Increasing evidences suggested that perirenal fat thickness (PrFT) was associated with metabolic risk factors, this study aimed to assess the association between PrFT and metabolic syndrome (MetS) in Chinese Newly-Diagnosed type 2 diabetes (T2DM), further evaluating the ability of PrFT in identifying Mets. Method: A total of 445 Chinese Newly-Diagnosed T2DM were enrolled into this study from January to June 2021. Demographic and anthropometric information were collected. PrFT was evaluated by CT scanning on Revolution VCT 64. Receiver operating characteristics (ROC) curves were conducted to assess the optimal cutoff value of PrFT in identifying MetS. Results: Overall, the prevalence of MetS was 58.2% in Newly-Diagnosed T2DM.Correlation analysis showed that PrFT was significantly correlated with metabolic risk factors (BMI, WC, TG, HDL-c, SBP, DBP, UA and HOMA-IR). PrFT was also shown to be independently associated with MetS after adjustment for other confounders, the ORs(95%CI) were 1.33(1.01~1.74) in men and 1.53(1.08~2.17) in women(P<0.05). ROC curves showed a good predictive value of PrFT for MetS, the the areas under the curve of PrFT identifying MetS were 0.895(95% CI 0.852~0.939) in men and 0.910 (95% CI 0.876~0.953) in women (P<0.001). The optimal cut-off values of PrFT were 14.6 mm (sensitivity: 83.8%, specificity: 89.6%) for men and 13.1 mm (sensitivity: 87.6%, specificity: 91.1%) for women. Conclusions: PrFT was significantly independent with MetS and showed a powerful predicting value for MetS, which suggested PrFT could be an applicable surrogate marker for MetS in Chinese Newly-Diagnosed T2DM.